Environmental and Human Contamination Patterns by Infective Resistant Forms in Rural Settings of Cameroon - Kenfack-Jiofack Sorel; Kame-Ngasse Ginette Irma; Ebogo-Belobo Jean Thierry; Mbafor Fidelia Lem; Nkengazong Lucia; Zebaze Togouet Serge (Current Innovations in Disease and Health Research Vol. 4, 2023)
Background: Environmental and human health assessments are among the different components of one health that is increasingly being used in addressing global health challenges around the world. Intestinal parasitic infections are endemic in Cameroon, affecting people of all age groups. The objective of this study was to determine the profile of environmental and human contamination patterns in the Ngovayang health area of the South Region of Cameroon. Methods: This cross-sectional prospective study was conducted from January to April 2020. Stool samples from participants aged 2 to 85 years were analyzed with Kato-katz and Formol-ether technics while Zinc-sulphate, modified formol-ether and Saline solution methods were used for soil samples for infective stages identification. Infestation rate and variables compared were done by the parametric and non-parametric tests. Results: Stool (141/302:46.7%) and soil (51/324:15.7%) samples were positive for pathogens forms including Ascaris lumbricoides (46/302:15.2%), Trichuris trichiura (47/302:15.7%), Hookworms (11/302:3.6%), Fasciola hepatica 1/302: 0.3%), Entamoeba histolytica/dispar (9/302:6.6%), Entamoeba coli (48/302:15.9%) and candida spp. (35/302:11.6%). Saline solution and formol-ether technics revealed significant pathogens in soil (p= 0.001) while pathogens were significantly identified by the formol-ether technic (p= 0.0001). Participants of [20-30] years had highest egg load. Significant variation of infestation trend were observed for A. lumbricoides (P=0.04), Trichuris trichiura (P=0.04), Hookworms (P=0.01), E. histolytica/E. dispar (P=0.02) and yeasts (P=0.01) within villages. High infection rate was observed in March and in all collection sites (23/108:21.3%) in soil samples with A. lumbricoides predominating (22/108: 20.4%). Conclusions: This findings show human and environmental contamination by infective forms of human pathogens. Soil contamination rate probably indicates the population is at risk. Awareness on WASH and prompt deworming is encouraged for a healthy human and environmental status.